Pediculus humanus capitis - Nutanson, Inna (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
Head lice infestation, or pediculosis capitis, caused by Pediculus humanus capitis, is a common health concern. In the US, where pediculosis capitis is the most prevalent parasitic infestation of children, 6 to 12 million people are affected every year. Pediculosis capitis remains confined to the scalp. Scalp pruritus is the cardinal symptom, although patients with lice can be asymptomatic. Pruritus with impetiginization should prompt the physician to look for lice or viable nits. All close contacts should be examined. Treatmentdirected at killing the lice and the ova should be considered only ifactive lice or viable eggs are observed. The three fundamental effective treatment options for head lice are topical pediculicides, wet combing, and oral therapy. Spraying or fogging a home with insecticides or pediculicides isnot recommended.
Keywords: kožne bolezni; zajedavci; zoonoze